Politik Hukum Negara Kesejahteraan Indonesia (Studi Tentang Kebijakan Regulasi dan Institusionalisasi Gagasan Kesejahteraan Sosial Ekonomi Masyarakat Nelayan di Jawa Tengah) - Djauhari Djauhari (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Various government’s policies implemented through Precedential Decrees (Keppres), Precidential Instruction (Inpres),  and Precedential Regulation (Perpres), since the New Order up to the Reformation Order, have brought about the  increase of the social welfare among fishermen, especially through the schemes such as Undeveloped Regions Precedential Instruction (IDT) and  Social Security Network (JPS). However, those schemes seem to  be an ad-hoc solution which does not relate functionally to the Act on Social Welfare (UU Kesejahteraan Sosial) and the Act on Fishery Profit Sharing (UU Bagi Hasil Perikanan). Consequently, the availability of a sustainable program on social welfare cannot be achieved  since the function of  a presidential policy different from the function of an act.